Social Aspects of Transnational Corporations’ Activities in the New EU Member States - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2012)
Water resources are among the most valuable resources of the natural environment. The sustainable and integrated management of these resources is the basis of European water policy. Pursuant to the Water Framework Directive, all waters in the European Union should achieve a state considered at least good by the year 2015. Just how this objective can be met continues to be a topic of discussions in some of the Member States. There exist serious problems and delays in performing and implementing the provisions of the Directive in most EU countries. What is more, the state of the water economy in several countries, including Poland, has been criticized by the European Commission. Many challenges stand before European water policy. They require solutions on a global and local level. This article presents current key problems and planned directions for EU water policy development, subjected to analysis and assessment. Note is taken on the newest initiative of the European Commission in the area of water policy, especially the plan for protecting Europe’s water resources—the Blueprint to Safeguard Europe’s Water Resources